Determination of air quality and noise levels in the mixed industrial and residential areas of Nilai, Negeri Sembilan , Malaysia - Norela Sulaiman; Hazila Abdul Samat; Maimon Abdullah (Universiti Kebangsaan Malaysia, 2006)
This study was carried out to determine the air quality in the mixed residential and industrial areas of Nilai, Negeri Sembilan based on the concentrations of sulphur dioxide (SO2) carbon monoxide (CO), nitrogen dioxide (NO2) and ozone (O3) gases as well as noise levels. Samplings were carried out for a total period of four days comprising two working and Monon-working days for each station from October 2004 until January 2005. Air Pollution Index (API) values showed that the air quality in these stations was moderately good. Secondary data were collected for PM10 The average concentration values of SO2 CO, NO2 and 03 were 0.024+0.021, 3.782±1.033, 0.0I3±0.009 and 0.026±0.008 ppm respectively. The results also showed that the concentrations of the pollutants were below their respective maximum permissible values stipulated by the Malaysian Department of Environment (DOE). Statistical analysis showed that there were no significant differences (p>0.05) of the pollutant levels between working days and non-working days. However, there were strong positive correlations between ozone gas and nitrogen dioxide levels (r=0.447, p<0.0l). There were a/so strong positive correlations between the concentration of co and the number of vehicles passing through (r= O. 690, p<0.0l). This study showed that the NO2 parameter was 92.35% close to the maximum permissible value set by the DOE. This could be due to anthropogenic activities. The noise levels recorded in this area were above the permissible limits set by the DOE.